2016
DOI: 10.1074/jbc.m116.726620
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement of the Extracellular Domain in Activation of Class B G Protein-coupled Receptors

Abstract: G protein-coupled receptors (GPCRs) from the secretin-like (class B) family are key players in hormonal homeostasis and are important drug targets for the treatment of metabolic disorders and neuronal diseases. They consist of a large N-terminal extracellular domain (ECD) and a transmembrane domain (TMD) with the GPCR signature of seven transmembrane helices. Class B GPCRs are activated by peptide hormones with their C termini bound to the receptor ECD and their N termini bound to the TMD. It is thought that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 38 publications
(78 reference statements)
16
59
0
Order By: Relevance
“…2a). Consistent with the previous report (16), in the absence of any ligand, WT GCGR has a very low basal activity, and addition of a membrane-tethered GCG (GCG-M) stimulated an approximately 30-fold increase in cAMP activity (Fig. 2b), which was approximately the same level of activation by exogenous GCG at saturated concentration (1 M GCG in Fig.…”
Section: Mutations At Phe-345 Are Sufficient To Induce Constitutive Rsupporting
confidence: 77%
See 3 more Smart Citations
“…2a). Consistent with the previous report (16), in the absence of any ligand, WT GCGR has a very low basal activity, and addition of a membrane-tethered GCG (GCG-M) stimulated an approximately 30-fold increase in cAMP activity (Fig. 2b), which was approximately the same level of activation by exogenous GCG at saturated concentration (1 M GCG in Fig.…”
Section: Mutations At Phe-345 Are Sufficient To Induce Constitutive Rsupporting
confidence: 77%
“…Ligand binding to the GCGR ECD rearranges the ECD to a "stand up" position and releases the ECD repression of the TMD, which then results in receptor activation. Although the stand up activation model fits well with the general framework of the two-domain mechanism for ligand binding and activation of class B GPCR, it cannot explain the requirement of the ECD in activation of GCGR and GLP-1R (16). In these two receptors, we have shown that their ECDs play a much more direct role in the receptor activation in addition to their role in ligand binding (16).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Preliminary studies have proposed that GPCR ECRs regulate receptor functions, likely including G-protein signaling, on binding to extracellular ligands (9,(23)(24)(25)(26)(27)(28)(29). Two complementary models for ligand-induced aGPCR activation have been proposed (Fig.…”
mentioning
confidence: 99%